Numerical investigation of mathematical non-dimensional constant representing smoothness in the Nusselt profile - Ansari, Emad; Siddiqui, M. Umair; Khan, Sher Afghan; Akhtar, Mohammad Nishat; Ilmi, Abu Bakar (Akademia Baru, 2020)
Cooling of devices using air-jet and other fluid impingement has acquired pace in the manufacturing and electronic device industries. The cooling of the surface using liquid jets is studied using the Nusselt distribution profile. The pattern of the Nusselt profile becomes non-uniform when some parameters are wrongly selected. This may lead to heating of some locations instead of cooling of the surface. Thus research for keeping the Nusselt profile uniform is a primary task. The Nusselt profile depends mainly on the Reynolds number (Re) and nozzle-target spacing (Z/d). Therefore, the current study numerically evaluates the value of constant, which is a ratio of Reynolds number and nozzle-target spacing (C = Re/ (Z/d)) up to which the Nusselt profile remains uniform. The value of constant C is found to be 7400. Also, the present work uses a computational model for study, which is validated using grid independence test and turbulence modeling.